Efeito da heterogeneidade ambiental sobre a diversidade de larvas de Chironomidae (Insecta: Diptera) em uma planície aluvial neotropical. - Pressinatte Junior, Sidnei (2011)
Sediment and water spacial patterns affect the aquatic community structure. Chironomidae larvae, in general, dominate zoobenthic community both in abundance and in species richness in the Paraná River floodplain. Here, we hypothesized that diversity and distribution of Chironomidae larvae is higher in more heterogeneous environment, considering the granulometric texture as surrogate of heterogeneity. Samplings were realized quarterly from February to December 2008 in 12 sampling stations. Chironomidae larvae were identified to lowest taxonomic possible level. Considering the number of taxa, we recorded a total of 66 morphospecies, belonging to three subfamilies. Density, species richness and Shannon-Wiener diversity were different between lotic and lenthic environments, with higher values in the former than in the latter. In addition, this difference was strengthened by the two DCA axes. The dominant species in lotic environments were Djalmabatista pulcher, D. sp.2, Endotribelos sp. 2, Paralauterboniella sp.1, Polypedilum (Polypedilum) sp. 1 e Tanytarsus sp.1, while lenthic environment were dominated by Tanypus stellatus, Chironomus sp. 5, Goeldichironomus pictus and Procladius sp. 2. The Shannon-Wiener diversity was applied to granulometric data and showed higher sediment diversity in the lotic environments. Thence, we do not reject our hypothesis and suggest that the diversity and distribution pattern of Chironomidae larvae may have been affected by sediment heterogeneity, due to the higher values of the assemblage attributes found in greater environment heterogeneity.